Solución del problema de la estabilidad material aplicando el método de sustituciones sucesivas para mezclas con equilibrios líquido – líquido y líquido – líquido reactivo (2011)
A version of successive substitution method suggested by Michelsen (1982a) is presented to analyze the material stability of multicomponent liquid mixtures (with and without reaction). The technique does not require numerical derivatives and is computationally easy to implement. Some examples of isothermal flash are illustrated for the n-amyl acetate + water + acetic acid mixture and reactive isothermal flash for the acetic acid + butyl alcohol + butyl acetate + water mixture. The results allow conclude that the Rachford and Rice algorithm converges without numerical problems when is initiated with the results of material stability test.